Effect of BI Rate and Profit Sharing Rate onFinancing Income Mudharabah at PT. Bank Muamalat Indonesia 2011-2015 Period - Deni Iskandar; Fitranty Adirestuty (Universitas Pendidikan Indonesia, 2018)
This study The purpose of this study is to find out how the BI Rate affects the mudharabah financing income, how the profit-sharing rate affects mudharabah financing income, and how to BI Rate and profit-sharing rate affect mudharabah financing income. This type of research is quantitative research, the method used in this study is associative research (relationship) supported by a document analysis approach, the place which is the object of research is PT Bank Muamalat Indonesia, the sample used is the monthly financial statement off PT Bank Muamalat Indonesia in 2011 period 2015 by using the purposive sampling method. The variables in this study are two variables: the independent variable (free) and the dependent variable (bound). There are two independent variables, namely BI Rate (X1) and Profit Sharing (X2) while independent while the dependent variable is Mudharabah Financing Income (Y). The type of data used secondary data obtained from the financial report published by BI, OJK, and through the official website of PT Bank Muamalat Indonesia. Data analysis shows that partially the BI Rate and Profit-Sharing Rate (TBH) have a positive and significant effect on Mudharabah Financing Income, as evidenced by the value of BI Rate variable 0,0024 0.05 and the prob value of the Rate of Sharing 0,0000 0,05. Taken together, the BI Rate and Profit Sharing variables have a significant influence on Mudharabah Financing Income, and this is evidenced by the value of prob F statistic 0,000, which is smaller than 0,05. The variable BI Rate and Profit Sharing Level has a contribution to explain Mudharabah Financing Income of 83,3% while the remaining 16,7% (100%-83,3%) is explained by other variables not examined or not included in this research model